MODIFICATION OF STARCH WITH ITACONIC ANHYDRIDE AND 2,3-PYRIDINEDICARBOXYLIC ANHYDRIDE - RENGGANIS NIM:10514037, DITA
Chemical modification of starch can be performed via several ways, such as esterifications and grafting copolymerizations. In this study, itaconic anhydride and 2,3-pyridinedicarboxylic anhydride, which one succinate anhydride derivates, are used as substituting agents. The esterification of starch was conducted as acid and base catalyzed reactions at 60 Ã‚Â°C for a reaction period of 3 hours, by varying the weight rasio between the substituting agents and starch. The resulting product were chacaterized by FTIR (Fourier-Transform Infrared Spectroscopy), 1H-NMR (Nuclear Magnetic Resonance), SEM (Scanning Electron Microscopy), and TGA/DSC (Thermogravimetric Analysis/Differential Scanning Calorimetry). FTIR spectrum for the esterified starch from the acid catalyzed reactions showed the ester group at 1720 cm-1 while esterified starch from the base catalyzed reactionss did not show the prominent vibration of ester group. 1H-NMR spectrum for the esterified starch showed proton signals of glucose residues at 3.28‒5.1 ppm. The proton signal at 6.1 ppm was for the itaconic anhydride starch and the proton signals at 7.6‒8.7 ppm for 2,3-pyridinedicarboxylic anhydride starch. The morphology of esterified starch was characterized by SEM which showed significant differences between starch and the modified starch. It indicated that the starch was successfully esterified. TGA/DSC characterization showed that starch had a higher thermal resistance (259 Ã‚Â°C) than the products. Based on the FTIR spectra, itaconic anhydride was more efficient in esterifying starch compared to 2,3-pyridinedicarboxylic anhydride. Itaconic anhiydride was further used in modifying starch via grafting copolymerization. The graft copolymer was synthesized using CAN (cerium ammonium nitrate) as an initiator at 80 Ã‚Â°C, for 3 hours, under N2 atmosphere. The product was characterized by FTIR and it showed the vibration of carbonyl group at 1708 cm-1.